2022
DOI: 10.3389/fonc.2022.934080
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of fatty acid and lactate metabolism–related genes for prognosis value, immune infiltration, and therapy in osteosarcoma patients

Abstract: Osteosarcoma is the most frequent bone tumor. Notwithstanding that significant medical progress has been achieved in recent years, the 5-year overall survival of osteosarcoma patients is inferior. Regulation of fatty acids and lactate plays an essential role in cancer metabolism. Therefore, our study aimed to comprehensively assess the fatty acid and lactate metabolism pattern and construct a fatty acid and lactate metabolism–related risk score system to predict prognosis in osteosarcoma patients. Clinical dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…Wu et al. [66] selected fatty acid and lactate metabolism-related genes to construct a prognostic prediction model that also had a significant effect on the tumor immune microenvironment, which had similarities with our study, but it is worth discussing that our study focused on a finer perspective of lactate metabolism and limited to lncRNAs, a popular target for a variety of cancers, to construct a prognostic prediction model with higher diagnostic value. The AUC values for predicting 1-, 3-, and 5-year survival in osteosarcoma reached 0.943, 0.927, and 0.947, respectively, compared with only 0.841, 0.750, and 0.750, respectively, in the model of Wu et al.…”
Section: Discussionsupporting
confidence: 58%
“…Wu et al. [66] selected fatty acid and lactate metabolism-related genes to construct a prognostic prediction model that also had a significant effect on the tumor immune microenvironment, which had similarities with our study, but it is worth discussing that our study focused on a finer perspective of lactate metabolism and limited to lncRNAs, a popular target for a variety of cancers, to construct a prognostic prediction model with higher diagnostic value. The AUC values for predicting 1-, 3-, and 5-year survival in osteosarcoma reached 0.943, 0.927, and 0.947, respectively, compared with only 0.841, 0.750, and 0.750, respectively, in the model of Wu et al.…”
Section: Discussionsupporting
confidence: 58%
“…7 G). The most lethal disaster and clinical problem for patient survival rate in OS is lung metastases [ 48 ]. The anti-metastasis effect of the biomaterials was assessed using pulmonary bioluminescence imaging and H&E staining.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to cells in normal tissues, tumor cells within tumors exhibit unrestrained growth, dysregulated differentiation, and senescence resistance, necessitating adaptation to uctuations in nutrient, carbon source, and oxygen supply in their environment. While the expression level and role of ACSS2 in tumor progression, including BC cells, remain controversial, there is consensus that lipid metabolism involving ACSS2 and its synthesis of acetyl-CoA directly impacts the survival and invasion of tumor cells [18][19][20][26][27][28][29][30]. Studies on breast ductal carcinoma cells have revealed that increased ACSS2 expression, triggered by insu cient oxygen supply, is regulated by the combined action of SREBP2 and HIF.…”
Section: Discussionmentioning
confidence: 99%
“…While the in uence of ACSS2 levels on cancer progression remains controversial to some extent, clinical data predominantly associate its upregulation with poor prognosis in multiple cancer patients [26][27][28][29][30]. In BC, ACSS2 levels have been reported to be lower than in mammary broma tissues.…”
Section: Introductionmentioning
confidence: 99%